Development of Internet-Based Instrumentation System for the Study of Superconducting Magnetic Levitation - Teh, Jia Yew (2003)
Computers can be utilized to control instruments, machines, motors, devices etc. to automate tasks. Presently, an automation system had been constructed and successfully used to conduct the physics experiments to study the levitation force in the Bi-Sr-Ca-Cu-O (BSCCO) high Tc superconductor series. This research project aims to improve the automation system. Two major improvements were made; first, converting the existing automation system into a Web based automation system and replacing the DOS based QBasic program with Windows based user interface . The Web based automation system can be remotely controlled and monitored by users in remote locations by using only their web browsers; as if they (the users) are sitting right in front of the automation system! This is achieved by programming the server computer (which was interfaced to the automation system) to load Java Applets containing the user interface required to control the automation system, into the remote user's web browser The Web based automation system is also capable of remote data acquisition or DAQ, whereby experimental data can be remotely acquired by the user through File Transfer Protocol (FTP). Three major types of test essential for the study of superconducting levitation forces were also integrated into the user interface. The tests are: detection of magnetic hysteresis, detection of stiffness loops for increasing distance and detection of magnetic stiffness for decreasing distance. Each test requires varying degrees of control over a stepper motor's movement. The stepper motor is the key component of the automation system and is used to vary the distance between the magnetic materials in small, controlled, steps of 0.05 mm per movement. Both the user interface and the Web based features were developed using a graphical programming language called LabVIEW. The Web based automation system was used to conduct a series of experiments to study the levitation forces of Cadium (Cd) doped Bi-Sr-Ca-Cu-O (BSCCO) high Tc superconductor series. Users are successful in logging into the automation system to control, monitor and acquire data remotely from the automation system in real time. The Web based automation system was successful in detecting magnetic hysteresis for all the superconductor samples measured. Further, magnetic stiffness loops were also detected over all samples. Analysis of the magnetic hysteresis and stiffness loops showed agreement with work done by Chang and Moon, two prominent researchers in the field of superconductor research.